Thoracal Paravertebral vs. Serratus Anterior Plane Block in Combination with COMBIPECS for Modified Radical Mastectomy - Utomo, Wandito Gayuh; Fitriani, Calcarina; Sudadi, Sudadi; Ali, Farhan (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2024)
Background: Breast cancer is one of the most common malignancies in women worldwide. Surgical options for breast cancer include modified radical mastectomy (MRM), in which the entire breast is removed but the pectoralis major muscle is spared. Routine anesthesia modalities for MRM include general anesthesia (GA), epidural blockade combined GA, and nerve blockade combined GA . Thoracic paravertebral block (TPVB) is still recognized as the gold standard analgesic procedure for breast surgery. However, TPVB is more difficult to perform with possible complications such as hypotension, pneumothorax, and unintentional spread of anesthetic agent to epidural space. Serratus anterior plane block (SAPB) is a promising new procedure that is relatively easier to perform and safer. Previous studies have reported its benefit in reducing the need of postoperative opioids and postoperative pain.Case illustration: We describe the case of 2 females with left breast cancer undergoing unilateral MRM, both with ASA class II. First patient was given TPVB, PEC 1, and PEC 2 (COMBIPECS). Second patient was given nerve block and guided ultrasonography using SAPB, PEC1, and PEC 2 (COMBIPECS). Each patient was sedated with a dexmedetomidine loading dose of 1mcg/kg/10 minutes, titration 0.2-0.4mcg/kg/hour. Both types of blocks provide adequate anesthesia. Ketorolac 30mg/8 hour was given post-operative. Both patients showed normal vital signs, and the same post-operative NRS of 0. No block related complication was found in both cases.Conclusions: TVPB and SAP combined with COMBIPECS have similar results in terms of post-operative pain score and minimal complication.